Stress-deformed state of the Earth crust of the Bug mining area in the section Gayvoron—Zavalye - Mychak, S. V.; Murovskaya, G. V.; Polyachenko, E. B.; Belskyi, V. M. (Geofizicheskiy Zhurnal, 2018)
Results of tectonic-physical studies of the upper part of the Earth mantle of the Bug mining area of the Bug block of the Ukrainian shield fulfilled in 2017 in the basin of the upper and middle course of the Southhern Bug river have been presented in the paper. The aim of the studies is examination of the rocks deformations character and reconstruction of paleostrains for subsequent plotting of geodynamic model of the Earth crust for the Bug mining area. Field tectonic-physical studies have been fulfilled by a structural-paragenetic method of tectonic-physics for different depth levels. For plotting stereograms for orientation of rocks jointing and other structural elements the program Stereonet was used. The rocks of the area are characterized by structural-textural anisotropy and are interrupted by numerous zones of polytectonites. The structural elements of the studied territory were mainly formed by the effect of rockslide deformational regimes with sub-horizontal position of the main (maximal and minimal) normal strains. At the early stages of right- and left-shift deformations of the Gaivoron-Zavalye block early flow cleavage and schistosity, linear and banded texture of rocks were formed. In zones of maximal rockslide deformations monocline and structural-textural elements (STE) are widely developed. Strain field calculated by STE is close to the strain field of the Kirovograd stage of faults formation. Overwhelming majority of fragile fissures of the study area have sub-vertical drop and two main spreading directions, the first one is sub-parallel to structural-textural elements and the second one is subnormal to them. The field calculated by fissure paragenesis corresponds to the younger Subbotsk-Moshorin stage of fracture formation of the Ukrainian shield.